Management of Exotic Poplars for Production of Quality Timber and Reducing Cotton Menace in Kashmir (J&K) - Gangoo, S. A.; Masoodi, T. H.; Murtaza, Shah; Islam, M. A. (Indian Forester, 2015)
Practicing lateral pruning as a management practice has given results that there is a significant increase in increment per cent in height of the poplar trees when they are laterally pruned up to 25 % clear bole, 75 % clear bole or 100 % clear bole. However, the pruning intensities do not make any difference in the height of trees when compared among themselves. The results also reveal that there is a significant effect on increment per cent in diameter over control. However, there is no significant effect on increment per cent in dbh among different pruning intensities. As there is significant difference in height and dbh due to various pruning intensities, the same is reflected by the volume of the trees. The maximum commercial volume is obtained in 100% pruning intensity which is 178% more over control followed by 25% and 50% pruning intensities which are significantly at par. Pruning management also reduces the number of female catkins considerably when trees are pruned up to 50%. The number of catkins gets reduced by 80%. Hence it is suggested that the poplar plantations should be intensively pruned leaving at least 50% clear bole to get knot free timber and reduce the cotton menace by 80% due to dispersal of seeds during the month of June and July. This pruning should be done in autumn and till the plantation achieves a height of 15 meters because up to this height the trees can be pruned without much effort.